Arginine Regulates Zygotic Genome Activation in Porcine Embryos Under Nutrition Restriction - Zhang, Tianrui; Zheng, Yingying; Kuang, Tianya; Yang, Lianyu; Jiang, Hailong; Wang, Heming; Zhao, Yicheng; Han, Rui; Che, Dongsheng (Frontiers in Veterinary Science, 2022)
Arginine has a positive effect on preimplantation development in pigs. However, the exact mechanism by which arginine promotes embryonic development is undefined. Here, single-cell RNA sequencing technology was applied to porcine in vivo preimplantation embryos from the zygote to morula stage, it was found that that the expression of arginine metabolism-related genes clearly changed from the 2-cell stage to the 4-cell stage, when zygotic genome activation (ZGA) occurs in porcine embryos. Further analysis showed that arginine metabolism-related genes are significantly correlated with key ZGA genes. To determine the function of arginine in porcine embryos during ZGA, the in vitro fertilization embryos were cultured in PZM-3 medium (0.12 mM arginine, Control group), a modified PZM-3 medium (0 mM arginine, Block group) and a modified PZM-3 medium supplemented with arginine (0.12 mM arginine, Block + Arg group). The results showed that the 4-cell arrest rate was significantly increased in the block group compared to the Control group (P < 0.05). The 4-cell arrest rate in the Block + Arg group was significantly decreased than that in the block group (P < 0.05). Meanwhile, the expression of ZGA marker genes and SIRT1 protein in 4-cell embryos was significantly decreased in the block group compared to the Control group, and their expression was significantly increased in the Block + Arg group. In addition, we observed that the glutathione (GSH), ATP levels, and lipid droplet contents were significantly increased, and the reactive oxygen species (ROS) level was decreased in the Block + Arg group compared to the block group. Compared with Control group, spermine content in culture medium and the mRNA expression of ornithine decarboxylase1 (ODC1) of embryos in the block group were significantly decreased (P < 0.05), and those in the Block + Arg group were significantly increased compared with the block group (P < 0.05). Moreover, when difluoromethylornithine (an inhibitor of ODC1) was added to the modified PZM-3 medium supplemented with arginine, the effect of arginine on ZGA was inhibited. In summary, our findings demonstrated that arginine may regulate ZGA under nutrition restriction in porcine embryos by promoting polyamine synthesis.